Relationship between Women`s Body Dissatisfaction, Sense of Coherence and Physical Activity - Audronė Dumčienė; Jolanta Gedvilienė; Vaidas Mickevičius (Lithuanian Sports University, 2018)
Background. Socio-cultural pressure exerted by the environment and the media makes the majority of women take care of their bodies. That is especially true in Western culture which promotes slimmer women in recent decades. Methods. Two questionnaires were used in this research: Body Shape Questionnaire and Sense of Coherence scale. Research participants were 79 women aged 34.6 ± 3.76 years. Results. After six months of regular fitness classes women's satisfaction of their body and their sense coherence level  improved  significantly.  Relations  between  body  shape  dissatisfaction  and  sense  of  coherence,  body  shape dissatisfaction and manageability, comprehensibility and manageability were found. Conclusions. Systematic fitness training positively affects women's satisfaction with their body. Understanding of  the  capability  of  controlling  their  body  shape  was  improved.  There  was  a  significant  relationship  between dissatisfaction with their body shape and sense of coherence. The effect of physical activity improved the values of all three components of the sense of coherence construct. The values of comprehensibility, meaningfulness and manageability indicators show that respondents may already have a better control of their sense of coherence. Keywords: women, body shape dissatisfaction, sense of coherence, physical activity